Pakistan resolution 75 years on: how wide is the gap between the dream and reality? - Ahsan, Abdullahil (Turkey Agenda, 2015)
Seventy five years have passed since Pakistan Resolution was adopted in Lahore on March 23, 1940. Ten years earlier poet-philosopher Muhammad Iqbal came up with the idea. Today many authors call Pakistan a failed state. The other day a journalist of Indian origin who works for a Malaysian daily asked me why Pakistan with most fertile lands of the Indian sub-continent suffers from such an economic quagmire. He thought as a student of history I might have an insight into the question – why is Pakistan is considered by many a failed today? Some international researchers have identified it “in a terminal decline”, foreseeing its “failure in five or six years”, or in “a deeply troubled state”. Many Pakistanis too are asking similar questions. A Pakistani journalist writing on the subject a few months back said, “The state has failed them (Pakistanis) miserably. If this dangerous drift continues the state will have failed itself too. So much so that it may forfeit the right to call itself a viable entity. Many patriots will take umbrage with this assessment but what else will Pakistan be when its key institutions fail to stand up for it?”. With the growth of extremism mostly in the name of religion, but also occasionally in the name of ethnicity and linguistic identity, the country has immersed into chaos. What went wrong in Pakistan? Were the founding fathers at fault while demanding Pakistan? ....